Phytosanitary status of agrocenoses, depending on their spatial and temporal localization, in relation to the nature protection area - Fedorenko, A. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
The influence of the remoteness of grain crops from the primeval nature protection biocenosis on their phytosanitary status and biodiversity, concerning distance and time.